1990
DOI: 10.1007/bf01063335
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption of phosphate in some semi-arid tropical Indian Vertisols

Abstract: Adsorption and desorption of phosphorus in soils are among the key processes governing its availability to crops. There have been very few studies on the phosphorus adsorption and desorption characteristics of Vertisols. The P adsorption and desorption characteristics of four Vertisols belonging to three agriculturally important soil series were studied. The amounts of P adsorbed by the soils at 0.2/xg ml -I equilibrium solution P concentration was low and ranged from 34.3 to 79.5/xg g-1 soil. The phosphate ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This agrees with the results of electroultrafiltration (EUF) extractions on some Indian Vertisols [19]. The additional P desorbed in the last of the CAER extractions was small in most samples and it had been thought that Resin-a might predict available P better than Resin8-P because it may be viewed as the maximum amount of CAER extractable P. A similar asymptotic estimate of resin extractable P was the best chemical assessment of available P in about 500 tropical soils [16], although most soils were acid.…”
Section: Sequential Extraction With Resinsupporting
confidence: 90%
“…This agrees with the results of electroultrafiltration (EUF) extractions on some Indian Vertisols [19]. The additional P desorbed in the last of the CAER extractions was small in most samples and it had been thought that Resin-a might predict available P better than Resin8-P because it may be viewed as the maximum amount of CAER extractable P. A similar asymptotic estimate of resin extractable P was the best chemical assessment of available P in about 500 tropical soils [16], although most soils were acid.…”
Section: Sequential Extraction With Resinsupporting
confidence: 90%
“…In alkaline Vertisols elsewhere, crystalline and amorphous Fe (oxy/hydr)oxides have been found to be correlated with P sorption and with the concentration of labile-P extracted by plants, bicarbonate extractable-P and anion exchange resin (e.g. Solis and Torrent, 1989), while Shailaja and Sahrawat (1990) found that sorbed P was easily desorbable from similarly low P-sorbing soils.…”
Section: Implications For Phytoavailabilitymentioning
confidence: 96%
“…More importantly, all the P sorbed remained in an easily desorbable form (Sahrawat and Warren, 1989;Shailaja and Sahrawat, 1990).…”
Section: Introductionmentioning
confidence: 98%